P91 Increasing tetracycline resistance in Neisseria gonorrhoeae in England: investigating possible clinic-epidemiological associations. (16th June 2022) - Pitt, Rachel; Merrick, Rachel; Donaldson, Hugo; Rayment, Michael; Day, Michaela; Cole, Michelle; Woodford, Neil; Fifer, Helen
Abstract : Introduction: Between 2015-2019 the prevalence of tetracycline resistant (tetR) Neisseria gonorrhoeae (NG) in the Gonococcal Resistance to Antimicrobials Surveillance Programme (GRASP) increased from 39.4% to 62.9% (41.6% to 75.0% in men who have sex with men (MSM)). We sought to investigate why tetR was increasing. Methods: GRASP data were matched to the GUMCAD STI surveillance system for individuals attending a large London sexual health clinic (SHC) between 2015-2019. Pearson's correlation was used to summarise associations between annual SHC attendances, bacterial STI tests performed, STIs diagnosed and attendance due to partner notification (PN), with NG tetR in the following year. Results: 887, 185 attendances at the SHC were analysed ( Table 1 ). MSM accounted for 50.9% attendances. Attendances decreased for heterosexual men and women (HSM&W) from 2015 to 2019 and increased for MSM. Bacterial STI tests performed decreased for HSM&W, whilst STI diagnoses increased (positivity 7.6% to 11.6%). Tests increased for MSM, however diagnoses decreased (positivity 26.8% to 17.8%). Attendance for PN increased marginally for all. TetR NG increased across all cohorts, most markedly in MSM (42.7% to 83.5%). A positive correlation with tetR NG in MSM was found between SHC attendances (Pearson's correlation r=0.91, p=0.03) and bacterial STI tests (r=0.94, p=0.02). No correlations were observed for HSM&W. Discussion: High-risk MSM are recommended to screen for STIs 3-monthly and in the PrEP era regular testing has become more common. This, in combination with increased usage of doxycycline for the treatment of other STIs, may account for the increase in tetR NG.